2018
DOI: 10.3168/jds.2017-14353
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of rumen pH by sodium bicarbonate and a blend of different sources of magnesium oxide in lactating dairy cows submitted to a concentrate challenge

Abstract: With the objective of evaluating the potential effects of sodium bicarbonate or a magnesium-based product on rumen pH and milk performance of dairy cattle exposed to a dietary challenge, 30 lactating Holstein cows (648 ± 67 kg of body weight; 44.4 ± 9.9 kg/d of milk yield; 155 ± 75 d in milk) were blocked by parity (9 primiparous and 21 multiparous) and randomly distributed to 3 treatment groups. One group received a total mixed ration (TMR) that acted as a control (CTR), a second group (SB) received the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
2
16
0
1
Order By: Relevance
“…If the challenging rumen environmental conditions were attenuated by the inclusion of these buffers, then the action of the supplemental yeast may have been hindered. In agreement with this possibility, after challenging high-producing cows by replacing forages with barley grain, Bach et al (2018b) reported that rumen pH was greater for cows fed 200 g/d of sodium bicarbonate or 100 g/d of a magnesium oxide-based product compared with cows not fed any buffer.…”
Section: Resultsmentioning
confidence: 69%
“…If the challenging rumen environmental conditions were attenuated by the inclusion of these buffers, then the action of the supplemental yeast may have been hindered. In agreement with this possibility, after challenging high-producing cows by replacing forages with barley grain, Bach et al (2018b) reported that rumen pH was greater for cows fed 200 g/d of sodium bicarbonate or 100 g/d of a magnesium oxide-based product compared with cows not fed any buffer.…”
Section: Resultsmentioning
confidence: 69%
“…When compared to control diets, greater levels of supplemental calcium carbonate or limestone (12 to 24 g/kg) reduced intake, milk yield or milk protein (Clark, Plegge, Davis, & McCoy, ; Rogers et al, , ). Supplementation with up to 8 g/kg magnesium oxide increased intake, milk yield or milk fat in some studies that used corn silage as the primary forage source (Erdman et al, ; Teh et al, ), but not in other studies that used different primary sources of forage (Bach, Guasch, Elcoso, Duclos, & Khelil‐Arfa, ; Holtenius, Kronqvist, Briland, & Spörndly, ; Stokes, Vandemark, & Bull, ; Thivierge et al, ). Inclusion of 40 g/kg magnesium oxide to corn silage based diets increased milk fat percentage without affecting yields of milk or milk fat (Xin, Tucker, & Hemken, ).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with limestone or calcium carbonate increased rumen pH and decreased butyrate in one study (Keyser, Noller, Wheeler, & Schaefer, ), but no effects were found by others (Clark et al, ; Rogers et al, ). Effects of supplementing magnesium oxide on rumen pH are also variable, with some observing no effect (Stokes et al, ), others observing an increase (Erdman et al, ) and others observing an increase dependent on the source of magnesium oxide or ration composition (Bach et al, ; Xin et al, ). Similar to the current study, Erdman et al () and Xin et al () found no effect of supplementing magnesium oxide on total rumen VFA concentration, although changes in the molar proportions of acetate, propionate, butyrate or isobutyrate have been observed (Erdman et al, ; Stokes et al, ; Xin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maintaining ruminal pH at the average level (5.8-7.2) is an essential factor to balance the rumen microorganisms between acid producers and consumers. In this context, buffering reagents and alkalizer (e.g., sodium bicarbonate, magnesium oxide, and calcium magnesium carbonate), direct-fed microbials, and malate supplementation may increase pH in the rumen and production when ruminants are fed with high-grain based diets [66,68] [69]. Marden et al [70] reported that the inclusion of 150 g of sodium bicarbonate increased total ruminal VFA concentration by 11.7% compared to the control diet fed to lactating cows.…”
Section: Control Of Acidosismentioning
confidence: 99%